2007
DOI: 10.2174/138161207779313614
|View full text |Cite
|
Sign up to set email alerts
|

Metallocarboxypeptidases: Emerging Drug Targets in Biomedicine

Abstract: Metallocarboxypeptidases (MCPs) are commonly regarded as exopeptidases that actively participate in the digestion of proteins and peptides. In the recent years, however, novel MCPs comprising a wide range of physiological roles have been found in different mammalian extra-pancreatic tissues and fluids. Among them, CPU, also known as thrombin-activatable fibrinolysis inhibitor (TAFI), has been shown to cleave C-terminal Lys residues from partially degraded fibrin, acting as inhibitor of clot fibrinolysis and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 110 publications
(148 reference statements)
1
86
0
2
Order By: Relevance
“…In our studies we have identified carboxypeptidase D, which belongs to a family of enzymes that proteolytically process peptides in the secretory pathway (Arolas et al 2007), as a modifier of Ab toxicity. Previous reports have identified carboxypeptidase B as an enzyme that may degrade Ab intracellularly (Matsumoto et al 2001) by processing its carboxy terminus (Hamazaki 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In our studies we have identified carboxypeptidase D, which belongs to a family of enzymes that proteolytically process peptides in the secretory pathway (Arolas et al 2007), as a modifier of Ab toxicity. Previous reports have identified carboxypeptidase B as an enzyme that may degrade Ab intracellularly (Matsumoto et al 2001) by processing its carboxy terminus (Hamazaki 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the limiting factor in this cleavage is the removal of Leu 10 , as extremely small amounts of angiotensin 1-9 are detected relative to the amount of angiotensin II (i.e. angiotensin [1][2][3][4][5][6][7][8]. Thus, removal of His 9 appears to proceed faster than removal of Leu 10 .…”
Section: Discussionmentioning
confidence: 99%
“…All metallo-CPs have structurally similar CP domains. In addition to the CP domain, all A/B members contain an N-terminal propeptide that is necessary for folding and is cleaved off upon enzyme activation (1,4). The majority of A/B and N/E enzymes are secreted and function outside of the cell.…”
mentioning
confidence: 99%
“…They play key roles in processes including the degradation of proteins within the digestive tract as well as in the biosynthesis of peptide hormones and neuropeptides (Sapio and Fricker 2014). Hence there is considerable interest in defining the distinct roles of the carboxypeptidases, which are recognized as potential drug targets (Arolas et al 2007). Indeed, elevated CPA4 expression has been linked with increased aggressiveness of cancers including prostate cancer and non-small lung cell cancer (Sun et al 2016, Witte et al 2000).…”
mentioning
confidence: 99%